2018
DOI: 10.1075/ssol.18008.vri
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements reveal readers’ sensitivity to deliberate metaphors during narrative reading

Abstract: Metaphors occur frequently in literary texts. Deliberate Metaphor Theory (DMT; e.g.,Steen, 2017) proposes that metaphors that serve a communicative functionasmetaphor are radically different from metaphors that do not have this function. We investigated differences in processing between deliberate and non-deliberate metaphors, compared to non-metaphorical words in literary reading. Using the Deliberate Metaphor Identification Procedure (Reijnierse et al., 2018), we identified metaphors in two literary stories.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 57 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…She suggests that understanding the processes of metaphorical transference makes for better appreciation of why metaphors can provoke such a varied range of negative and positive responses. De Vries et al (2018) are also concerned with the way readers react to metaphors. They utilise eye-tracking techniques to assess to what extent readers are ‘sensitive’ to the presence of metaphors and, if so, how this affects their experience of the literary narrative.…”
Section: Cognitionmentioning
confidence: 99%
“…She suggests that understanding the processes of metaphorical transference makes for better appreciation of why metaphors can provoke such a varied range of negative and positive responses. De Vries et al (2018) are also concerned with the way readers react to metaphors. They utilise eye-tracking techniques to assess to what extent readers are ‘sensitive’ to the presence of metaphors and, if so, how this affects their experience of the literary narrative.…”
Section: Cognitionmentioning
confidence: 99%
“…For instance, de Vries and colleagues showed that participants that had shortest eye gaze durations when reading metaphors in a literary text, reported to be the most absorbed in the narrative. Moreover, these participants liked the story more than participants who did spend more time on the metaphors [49]. Jacobs in his model of poetic reading associates foregrounding with deepened processing, as reflected in slower reading [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, de Vries and colleagues showed that participants that had shortest eye gaze durations when reading metaphors in a literary text, reported to be the most absorbed in the narrative. Moreover, these participants liked the story more than participants who did spend more time on the metaphors [49]. Jacobs in his model of poetic reading associates foregrounding with deepened processing, as reflected in slower reading [29,30].…”
Section: General Likingmentioning
confidence: 93%